Causes of Drug Abuse In Youth: Case of Mid-Western Region of Nepal - Pathak, Dhanush Chandra; Pokharel, Binod (Journal of Advanced Academic Research, 2018)
Drug abuse is one of the serious social problems in Nepal and elsewhere for a long time. Drug abuse has several effects over the human life. Burgeoning unemployment, broken family, crime, depression, love failure, formation of peer group, mass media are major problems faced by the youth of the country. This paper explores the causes of drug abuse among youth in Mid-Western Region of Nepal. Quantitative research method was used to draw the data from 252 respondents. Simple random sampling technique was used to select the respondents of different rehabilitation center of Surkhet, Banke and Dang District. Data were analyzed by using chi-square statistical tools. Drug causes have covered the psychological, peer pressure, school/ college, socio cultural and mass media causes of drug abuse. Among them, majority respondent responded causes of drug abuse is bad relationship with family, to feel relax, failed in exam and films stars and idols which are shown on television.